Fungsi Kantor Pertanahan Sebagai Pelaksana Percepatan Pendaftaran Tanah Sistematis Lengkap - Fitrian Fitrian (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2021)
This study aims to determine and explain criminal law policies in tackling illegal logging crime and to find out the inhibiting factors of criminal law policies in tackling criminal acts of illegal logging in the Lambusango forest. Data collected in this study are primary and secondary legal materials and tertiary legal materials. Primary legal materials are binding legal materials in the from of laws ans regulations as well as other legal materials relating to criminal law policies in tackling illegal ligging in the Lambusango forest. Then what is meant by secondary legal materials are materials that provide clarity about primary legal materials such as book written by legal ecperts on criminal law policies in tackling illegal logging in the Lambusango forest. Whereas what is meant by tertiary legal materials are materials that provide instructions or explanations for primary legal materials and secondary legal materials, such as dictionaries and indexes. The data that has been obtained as a result of the study are analyzed using qualitative analysis, which illustrates the facts that are based on research that has been done in the from of a systematic description by explaining the relationships between various types of data. After the analysis is carried out, conclusions can be drawn using the inductive method to.